2017
DOI: 10.1021/acs.chemmater.7b00599
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant-Templating of Zeolites: From Design to Application

Abstract: Surfactant-templating is one of the most effective and versatile synthetic strategies for the construction of well-defined porous architectures in solids. Though the principles of molecular self-assembly were disclosed in biological systems since long, the use of amphiphiles to generate porous architectures in inorganic matter has merely emerged at the very end of the 20 th century. The present review proposes a voyage from the early developments of surfactanttemplating for designing ordered mesoporous solids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
97
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 128 publications
(100 citation statements)
references
References 144 publications
3
97
0
Order By: Relevance
“…A direct synthesis in the presence of mesoporogen structure directing agents (SDA) molecules provides a possibility to overcome issues mentioned above . These soft templating procedures offer the opportunity to tune the mesopore system …”
Section: Introductionmentioning
confidence: 99%
“…A direct synthesis in the presence of mesoporogen structure directing agents (SDA) molecules provides a possibility to overcome issues mentioned above . These soft templating procedures offer the opportunity to tune the mesopore system …”
Section: Introductionmentioning
confidence: 99%
“…In order to realize the full potential of mordenite the development of secondary porosity within its structure has been put forward . This approach allows to reduce the diffusion path length (hence increase catalytic activity, selectivity and stability) and at the same time increase the accessibility of bulkier molecules to the active sites . In this quest, a multitude of strategies have been proposed with the aim at achieving mordenite featuring hierarchical porosity .…”
Section: Introductionmentioning
confidence: 99%
“…[4] This approach allows to reduce the diffusion path length (hence increase catalytic activity, selectivity and stability) and at the same time increase the accessibility of bulkier molecules to the active sites. [5][6][7] In this quest, a multitude of strategies have been proposed with the aim at achieving mordenite featuring hierarchical porosity. [8] Most of these strategies are related to post-synthetic modifications.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, many researchers have used this kind of new gemini surfactant to synthesize a series of hierarchical molecular sieves. The studies showed that after adding a gemini quaternary ammonium salt cationic surfactant, several attractive features like control of pore size, surface areas (especially areas of mesopores) and interconnection of various pore structures could be improved . So far, gemini quaternary ammonium salt surfactants have mainly been used to produce MFI, BEA and MOR zeolites, rather than analcime (ANA) zeolite.…”
Section: Introductionmentioning
confidence: 99%